Food Insecurity and Its Cardiovascular Implications in Underresourced Communities - Esther Porras‐Pérez; Juan L. Romero‐Cabrera; Alberto Díaz‐Cáceres; Alejandro Serrán‐Jiménez; Javier Arenas‐Montes; Patricia J. Peña‐Orihuela; Isabel De‐Castro‐Burón; Antonio García‐Ríos; José D. Torres‐Peña; María M. Malagón; Javier Delgado‐Lista; Jose M. Ordovás; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Food insecurity is linked to poorer cardiovascular health (CVH) outcomes, particularly in underresourced communities, where social determinants of health play a critical role. Despite the recognized connections, there remains a lack of empirical evidence delineating the implications of food insecurity on CVH. CVH, a broader concept than cardiovascular disease, encompasses the overall well‐being of the cardiovascular system and is supported by favorable lifestyle choices and physiological metrics. Particularly in underresourced communities, the study of CVH could provide valuable insights for early intervention and targeted public health initiatives. This study aimed to fill this knowledge gap. Methods and Results We conducted a cross‐sectional analysis of baseline data from the E‐DUCASS (Educational Strategy on a Vulnerable Population to Improve Cardiovascular Health and Food Insecurity) program (NCT05379842), a 24‐month randomized study targeting participants at risk for food insecurity. CVH was assessed using the Life's Essential 8 score. The sample included 451 participants aged 12 to 80 years, stratified by age (30.6% children [aged 12–19 years], 35.9% young adults [aged 20–39 years], and 33.5% adults [aged 40–80 years]) and sex (42.1% men and 57.9% women). The mean CVH score was 65.1 (95% CI, 63.9–66.4), with diet, physical activity, nicotine exposure, and body mass index being the lowest‐scoring metrics. Food insecurity significantly influenced CVH; those participants with severe food insecurity had lower CVH scores than those without (effect size, −2.83 [95% CI, −5.10 to −0.56]; P<0.05). Conclusions Our findings highlight the negative association between food insecurity and CVH in underresourced Mediterranean communities. These results underscore the need for strategies aimed at reducing cardiovascular risk, potentially through health literacy programs like E‐DUCASS, that focus on improving lifestyle and alleviating food insecurity. Registration URL: https://www.clinicaltrials.gov; Unique Identifier: NCT05379842.